Pool Finance Economic System - Kayadibi, Saim (IIUM Press, 2011)
This paper aims at critical examination of the Pool Finance Economic System (PFES). As it is known that usury (riba) basically is a making money method from money without encountering a risk and an effort. Conventional banks offer loans to institutions of state in exorbitant interest rates with the collected loans from different institutions of the same state in cheap interest rates. Therefore, the conventional banks augment their money without risk through lending an Institution’s money to other sector of the same institution. This tricky usury method makes them even more powerful in economic and finance life which led them to force on government and a state on any issue for their interests. As Thomas Jefferson claimed that the Conventional banks and banking institutions could become more dangerous and threatening than modern armed forces. There is no much works have been done about this financial system in regards to method, implementation, ways to success and free-interest quality. Therefore this paper will try to explore the reality of the sensitive finance issue of Pool Finance Economic System for the sake of Muslim Ummah inshaAllah.